The Modification of Ni-supported Gamma Alumina with Yttrium as an Oxygen Carrier for Chemical Looping Combustion - Mohamed@Mohd Ghazali, Nur Adibah (2022)
With the recent advancement of the chemical looping combustion (CLC) industry, the development of materials with high stability and high oxygen transport capacity (OTC) has become a research hotspot.